Analisis Tindak Tutur Komisif pada Monolog Demokrasi Karya Putu Wijaya - Anggia Puteri; Muhammad Khoir Pahlepi; Rika Arini; Ahmad Bukhari Nasution; Nurul Hijrah; Diva Azzurra; Adelia Fitri Anggita; May Sarah; Jelita Teresia Br L. Tobing (Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to analyze commissive speech acts in Putu Wijaya's democracy monologue. Commissive speech act is a speech act that binds the speaker to carry out what is mentioned in the speech. This research uses descriptive qualitative method which is a research that describes the phenomenon or situation that is observed objectively. The subject of this research is the video monologue